Food Products Evolution: Innovation Drivers and Market Trends - Tarabella, Angela (SpringerBriefs in Food, Health, and Nutrition, 2019)
Modern awareness of nutrition issues can be understood correctly if considered the destination of a historic journey, the critical aspects and outcomes of which have led to the current situation. In fact, over time there have been changes to scientific knowledge, food availability and processing and preservation methods. Commercial exchange has increased considerably between the countries of the world - so much so that it has defined a completely different scenario to the past and has influenced food availability, distribution models, preservation methods and the composition of individual foodstuffs. The products consumed on a daily basis throughout the world in industrialised countries have undergone review by the food industry, incorporating great aspects of innovation that make them highly different in their structure, content and even the packaging that protects and contains them. After covering the subject of innovation in the food sector, this Brief of work willdiscuss the various first- and second-generation product categories distributed in Europe starting from the period of post-war reconstruction, in order to illustrate the reasons that led to their birth and development on the market. Specific examples are shown for each proposed class, including highlights of their properties, technologies, innovation potential, related regulations, and distinctive features.